Implementation of Interactive Multimedia: A Solution to Improve Learners' Understanding in Islamic Education Learning - Humairo, Aisyatul; Ubaidillah, Ubaidillah; Anshari, Zainal; Nofiyanata, Dwi (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
The use of media in learning the Quran Hadith is very important to increase student interest and understanding. The right learning media can help students focus more, reduce boredom, and make it easier for them to understand and apply the material to everyday life. This study aims to analyze how the effect of using media in Islamic education on students' understanding. The method used is mixed methods with the type of classroom action research model Kemmis and McTaggart consisting of planning, implementation, observation, and reflection stages. Data sources were obtained through observation, interviews, tests, and documentation. Research instruments included student activity observation sheets, comprehension tests, interview guides, and learning documentation. Data analysis was carried out qualitatively and quantitatively, through the stages of data reduction, tabulation, interpretation of test results, and conclusion drawing. Data validity was tested using triangulation techniques and instrument validation. The results showed that the acquisition of pre-cycle test results obtained an average of 43%, then in cycle I obtained an average score of 63% while in cycle II obtained an average score of 83% in understanding Alquran Hadith lessons, the matter indicated an increase and obtained a good category in the predetermined interval class. These results can be concluded that the use of interactive multimedia can improve student understanding of Alquran Hadith subjects.